2018
DOI: 10.31436/imjm.v17i1.826
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Perception Versus Body Weight Status: How Good is The Agreement?

Abstract: Introduction: Body weight perception is an important underlying psychological factor associated with body weight. Overemphasis on thinness among adolescents can lead to unhealthy dieting practices and eating disorders, whereas underestimation of body weight may increase risk of the development of overweight and obesity. This study measured the agreement between body weight perception and body weight status (BMI) among late adolescents in Kuantan. Materials and Methods: A cross-sectional study was conducted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A score of 80 and below corresponded to "no concern with body shape", score of 81 to 110 corresponded to "slight concern with body shape", score of 111 to 140 corresponded "moderate concern with body shape" and score of 141 and more corresponded to "marked concern with body shape" (17). The BSQ shows good concurrent validity with Eating Attitude Test (EAT) and also Body Dissatisfaction subscale of Eating Disorder weight and those whom were obese identified themselves as overweight (7). Body shape misperception can lead to body image dissatisfaction/concerns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A score of 80 and below corresponded to "no concern with body shape", score of 81 to 110 corresponded to "slight concern with body shape", score of 111 to 140 corresponded "moderate concern with body shape" and score of 141 and more corresponded to "marked concern with body shape" (17). The BSQ shows good concurrent validity with Eating Attitude Test (EAT) and also Body Dissatisfaction subscale of Eating Disorder weight and those whom were obese identified themselves as overweight (7). Body shape misperception can lead to body image dissatisfaction/concerns.…”
Section: Methodsmentioning
confidence: 99%
“…Besides traditional mass media such as films, television and magazines being a factor in body shape concern (whereby exposure to thin-ideals in all forms media exposure was associated with body image dissatisfaction) (9), in this current age of internet and social media such as Facebook® and Instagram®, this two new modern forms of mass media has been reported to be a factor for body shape concerns (10,11). Previous local literatures have looked at prevalence of body shape concerns not only among the Malaysian adolescents (12) but also among students in higher learning institutions (7,8) and even among university undergraduate students including those from the medical and allied health programs (2,13). However it did not assess whether the duration of years in medical program nor the characteristics of modern mass media (internet and social media platforms) influences was a factor for body shape concerns.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research revealed that body weight and shape concerns could play a role in linking obesity and psychosocial impairment. These findings suggest that in the clinical care of obesity, weight perception should be targeted to enhance physical and psychosocial outcomes (Badrin, Daud & Ismail, 2018;Quaidoo, Ohemeng & Amankwah-Poku, 2018;Jamani et al, 2018).…”
Section: The Prevalence Of Obesity and The Socio-demographic Informat...mentioning
confidence: 97%
“…underweight, normal weight, overweight and obese. BMI values are independent of age and applicable for both males and females (binti Jamani et al,2018). Florido et al reported that when physical activities are increased, the chances of having cardiac injury or becoming obese are lessened.…”
Section: Introductionmentioning
confidence: 99%